Staging violence gender and social control in Jácaras and Entremese - Miguel Magro, Tania de (Routledge, 2021)
Staging Violence explores gender violence in Spanish early modern short theater. This book deals with domestic violence against women, extortion of prostitutes, and violence against men who display non-conventional forms of masculinity. The author argues that many'jácaras'and'entremeses'stage subversive discourses that repudiate or complicate official narratives of gender and the use of violence as a tool for achieving gender compliance. Short comic pieces are read against comedias. Each section of the book is expertly contextualized through an overview of the legal and moral contexts and the analysis of a variety of primary sources (law codes, manuals of conduct, church rulings, transcripts of civil and religious trials, and medical manuals) as well as statistical information. Staging Violence invites the reader to consider the transgressive potential of performance. As the first monograph entirely dedicated to the study of gender in this genre, this book is a vital resource for students and scholars interested in gender studies and theatre.